The ecological and genetic basis of convergent thick‐lipped phenotypes in cichlid fishes. Issue 3 (11th October 2012) - Colombo, Marco; Diepeveen, Eveline T.; Muschick, Moritz; Santos, M. EMILIA; Indermaur, Adrian; Boileau, Nicolas; Barluenga, Marta; Salzburger, Walter
Abstract The evolution of convergent phenotypes is one of the most interesting outcomes of replicate adaptive radiations. Remarkable cases of convergence involve the thick‐lipped phenotype found across cichlid species flocks in the East African Great Lakes. Unlike most other convergent forms in cichlids, which are restricted to East Africa, the thick‐lipped phenotype also occurs elsewhere, for example in the Central American Midas Cichlid assemblage. Here, we use an ecological genomic approach to study the function, the evolution and the genetic basis of this phenotype in two independent cichlid adaptive radiations on two continents. We applied phylogenetic, demographic, geometric morphometric and stomach content analyses to an African (Lobochilotes labiatus) and a Central American (Amphilophus labiatus) thick‐lipped species. We found that similar morphological adaptations occur in both thick‐lipped species and that the 'fleshy' lips are associated with hard‐shelled prey in the form of molluscs and invertebrates. We then used comparative Illumina RNA sequencing of thick vs. normal lip tissue in East African cichlids and identified a set of 141 candidate genes that appear to be involved in the morphogenesis of this trait. A more detailed analysis of six of these genes led to three strong candidates: Actb, Cldn7 and Copb. The function of these genes can be linked to the loose connective tissue constituting the fleshy lips. Similar trends in gene expression between African and Central American thick‐lipped species appear to indicate that an overlapping set of genes was independently recruited to build this particular phenotype in both lineages.